Innovation Strategy to Reduce Child Marriage Rate in Wajo, South Sulawesi Province, Indonesia - Sangkala Sangkala; Nuralamsyah Ismail (Jurnal Manajemen Pelayanan Publik, 2023)
The Indonesian government has made child marriage a priority program that must be overcome. In addition, in 2021, Wajo (regency) became the area with the highest number of child marriage cases in South Sulawesi, with 706 cases. It came to be the main problem of this study; how the Wajo Regency government of South Sulawesi Province reduced the number of child marriages to the remaining 305 (60%) cases led to be the essential matter. The purpose of this study is to describe and analyze how strategy innovation is carried out. Through a qualitative approach with in-depth interview methods and FGDs to relevant stakeholders and supported by available supporting data strategy innovation is carried out by the Wajo government. The results showed that the success of the strategy was supported by various factors, which as a strong commitment from the Regent, refocusing all types of activities and funding, forming a team to reduce the number of child marriages, involving quite a lot of stakeholders from various circles, innovative regulatory support, administrative sanctions, and social sanctions for families and couples who will marry. So it can be concluded that the strategic innovation was created because the Regent was able to utilize all resources and the involvement of various actors outside his government to support efforts to reduce the rate of child marriage in his region.